Sensory test Quality of White Tofu Nuggets and Sumedang Tofu Nuggets - Hilza Mussi Faradilla; Cici andriani; Rahmi Holinesti; Sari Mustika; Riski Gusri Utami; Yolanda Intan Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
The high public demand for healthy and economical fast food encourages innovation in plant-based food products, one of which is tofu nuggets. White tofu and Sumedang tofu as potential raw materials have different physical and chemical characteristics. However, research analyzing their impact on nugget quality is still limited. This study aims to analyze the differences in the quality of nuggets produced from the use of white tofu and Sumedang tofu. This study used a pure experimental method (true experimental) with a completely randomized design (CRD). The treatment consisted of two variables, namely white tofu nuggets (X1) and Sumedang tofu nuggets (X2). Primary data were collected through organoleptic tests conducted by 15 semi-trained panelists to assess the quality of the aspects of shape, color, aroma, texture, and taste. Data analysis was performed using the Independent Sample t-Test. The results showed a significant difference in quality (p<0.05) between the two treatments in terms of volume, inner color, and texture. Nuggets made from Sumedang tofu exhibited superior qualities in terms of denser volume, a more yellowish-white interior, and a softer, chewier texture. Conversely, no significant differences were found in shape, outer skin color, aroma, or flavor. In conclusion, the type of tofu used as the base ingredient significantly influences the volume, inner color, and texture of tofu nuggets. The use of Sumedang tofu resulted in nuggets with several better sensory characteristics than white tofu.